Evaluation of Coronary Artery Luminal Diameters in Patients with Pulmonary Arterial Hypertension - Ufuk Yildirim; Gulten Taskin; Meliyke Hatun Baser; Burak Tugmen; Busranur Yaliniz; Ilkay Camlidag; Murat Meric (Medicina)
Background and Objectives: Recent studies have demonstrated that pulmonary arterial hypertension (PAH) is a vascular disease that extends beyond the pulmonary vasculature. PAH has been associated with increased intramural coronary arteriolar medial thickness and decreased coronary arteriolar luminal area in both human and experimental models of the disease. The objective of this study was to assess the luminal diameter of epicardial coronary arteries in patients with PAH. Materials and Methods: Fifty patients with PAH who underwent cardiac computed tomography (CT) angiography at our center were included in this retrospective study. Fifty patients without pulmonary hypertension matched for age, sex, and coronary dominance were also included. Coronary artery luminal diameters measured by cardiac CT angiography were compared between the groups, in addition to baseline characteristics and standard cardiac measurements. Correlation analysis was also performed. Results: The diameters of the left main coronary artery, left anterior descending artery, and left circumflex artery were comparable between the groups. However, the right coronary artery (RCA) diameter was found to be greater in the PAH group (3.51 ± 0.66 mm vs. 3.02 ± 0.49 mm, p < 0.001). The RCA diameter exhibited a positive moderate correlation with the main pulmonary artery diameter (R = 0.517, p < 0.001), right atrial area (R = 0.515, p < 0.001), and right ventricular diastolic diameter (R = 0.506, p < 0.001). Conclusion: PAH may be associated with an increase in the RCA diameter.